Digital Communication Strategies of Homeless Accounts In Building Engagement on Tiktok Platform - Rakyta Azalya Maura Asrie; Wahyu Budi Priatna (Communica : Journal of Communication, 2026)
This study examines the digital communication strategies of "homeless accounts" informal, anonymously managed entities on TikTok in building substantial audience engagement within Indonesia's digital landscape. Addressing a significant gap in literature regarding non-traditional media actors, the research employed qualitative methods combining digital ethnography and content analysis of 10 purposively sampled accounts over three months. Findings demonstrate that these accounts strategically leverage trending content formats, emotional storytelling, and interactive platform features to foster engagement. Their content portfolio primarily consists of viral themes, local information, and inspirational narratives, consistently enhanced with trending audio-visual elements for optimal algorithmic visibility. Core communication strategies are built upon authenticity, emotional resonance, and dialogic community management, effectively cultivating digital empathy and co-creation among followers. The study reveals that effective digital communication can be successfully cultivated outside traditional media infrastructures through strategic application of platform-specific features and authentic narrative techniques. This represents a modern form of citizen journalism that thrives on relational trust rather than institutional credibility. However, this operational model presents significant challenges regarding accountability and potential misinformation spread, necessitating enhanced digital literacy initiatives and platform-supported verification mechanisms. This research contributes valuable insights into how informal digital actors cultivate influence and community trust beyond institutional boundaries, offering important implications for understanding evolving digital communication paradigms in platform societies.